2011
DOI: 10.1111/j.1442-9993.2011.02319.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between native and invasive gecko lizards in tropical Australia

Abstract: Invasive geckos of the genus Hemidactylus (Gekkonidae) are spreading rapidly through urban environments in many tropical and subtropical parts of the world. The invaders have caused rapid declines in native gecko abundance in some areas, but their interactions with Australian native species remain unknown. In a small rural village near Darwin, we found that Hemidactylus frenatus is abundant around both lighted and unlighted buildings, but rarely found in surrounding bushland. It is sympatric with the larger Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
(35 reference statements)
0
18
0
1
Order By: Relevance
“…When sympatric with native gecko species in urban environments, it is typically the most aggressive and is likely to displace them (Csurhes and Markula 2009), although it may be competitively subordinate to larger native species such as Gehyra australis (Yang et al 2012). Stringent quarantine protocols have been developed for operations on Barrow Island (Chevron 2011) and these could be adapted for use on Kimberley islands in conjunction with an education campaign targeting tourist operations, Aboriginal communities and the resource industry.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…When sympatric with native gecko species in urban environments, it is typically the most aggressive and is likely to displace them (Csurhes and Markula 2009), although it may be competitively subordinate to larger native species such as Gehyra australis (Yang et al 2012). Stringent quarantine protocols have been developed for operations on Barrow Island (Chevron 2011) and these could be adapted for use on Kimberley islands in conjunction with an education campaign targeting tourist operations, Aboriginal communities and the resource industry.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…One hypothesis for this pattern is that the invasive geckos actively exclude native geckos from lighter areas, where insect abundance is greatest (Petren et al 1993). Cisterne & L. Schwarzkopf, unpublished, 2013), as is another native house gecko, Gehyra australis (Yang et al 2012). Adult G. dubia are larger than adult H. frenatus (Wilson & Swan 2013), and in dyadic encounters are behaviourally dominant to the introduced species (A.…”
Section: Discussionmentioning
confidence: 99%
“…Asian house geckos have been implicated in the declines of other geckos on several islands (Petren et al 1993;Case et al 1994;Petren & Case 1996, including the near extinction of island-endemic Nactus geckos (Cole et al 2005). Newbery & Jones 2007;Yang et al 2012). Shine 2010), few studies have investigated interactions between H. frenatus and native Australian geckos (Hoskin 2011).Those studies that have investigated these interactions have found conflicting results (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…has previously been hypothesised to have an urban association (Anjos et al 2008) but without supporting evidence. Asian house geckos occur near buildings (McKay et al 2009, Hoskin 2011, Yang et al 2012), as do many cockroach species (Bell and Adiyodi 1982, Booth et al 2011). Increased rates of parasitism in urban environments (Bradley and Altizer 2007) can be explained by two main processes, which we discuss below.…”
Section: Discussionmentioning
confidence: 99%